An umbrella review of meta-analyses on the low-FODMAP diet in IBS - Bogdanowska-Charkiewicz, Dagmara; Malinowska, Urszula; Daniluk, Jarosław (Frontiers in Nutrition, 2026)
This umbrella review systematically evaluated the effects of the low FODMAP diet on irritable bowel syndrome (IBS) through 192 studies retrieved from PubMed, Web of Science, Cochrane Library, and Scopus up to January 2025. All meta-analyses and evaluation criteria adhered to PRISMA guidelines. The quality of the included meta-analyses was evaluated by AMSTAR-2. The effect size was expressed as a standardized mean difference, odds ratio, or relative risk, as available. Pooled analysis was based on a random-effects model. Sixteen meta-analyses qualified for the final statistical analysis (141 studies included, 9,904 patients), all of which concerned patients with IBS. Analysis of evidence showed that the low FODMAP diet in IBS patients significantly reduced symptom scores on the IBS Symptom Severity Scale (IBS-SSS) (standardized mean difference (SMD) = −0.599, 5 meta-analyses, 3,761 patients) and improved quality of life (SMD = 0.259, p < 0.0001, 5 meta-analyses, 3,576 patients). No significant effect was found on abdominal pain, stool consistency, stool frequency, or microbiota. For bloating, the pooled analysis was not possible due to different measures in the source meta-analyses. The placebo effect was not taken into account in most of the meta-analyses included in the umbrella review. A low FODMAP diet reduces symptoms and improves quality of life in patients with IBS. The results should be approached with caution, as they may be influenced by psychological factors related to the observation itself. As blinding or placebo-controlled conditions are inherently impossible in dietary interventions of this type, it is impossible to decide whether symptom reduction is caused strictly by diet or by non-specific or expectancy-related effects. Further methodologically reliable studies on the effectiveness of the low FODMAP diet in IBS are still needed.